EFFECT OF SHORT AND LONG DURATION NADA YOGA MEDITATION ON HEART RATE OF PARA YOGA ATHLETES - Tewani, Dakshata; Singh, Vikram; Joshi, Navdeep; Singh, Surender (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction: Heart rate is a fairly good indicator of health-related physical fitness and is often used by fitness and yoga trainers before, during, and after their training sessions. “Divyang Jana”, a term often used to refer to persons with disabilities (PwD) are equally and sometimes more prone to having elevated heart rates because of external and internal conditions beyond their control. This study was undertaken to evaluate the role of NADA Yoga Meditation (22 minutes) in improving the important physiological parameter heart rate (HR) in visually impaired (VI) para yoga athletes of Uttarakhand. Method: 52 para-yoga athletes were divided into two groups of which one group did Meditation and the other did not. HR-1 (pre-intervention, HR-2- after one week, and HR-3 after 2 weeks of the intervention were measured in beats per minute offline (first week) and online (second week) NADA meditation training. Result: At the end of the study significant decrease in HR-2 and HR-3 was seen in the para yoga sports persons who practiced Meditation as compared to the non-practicing group (control group) after controlling for the covariate HR-1 (pre-intervention heart rate). Discussion: The results were interpreted using MANCOVA and concluded that NADA yoga meditation was effective in reducing the heart rate mediated anxiety levels of yoga para-athletes in just 2 weeks and was found to be effective not only in just a week but also after 2 weeks of NADA Yoga meditation training done for 22 minutes each. Further, it can be argued that NADA yoga meditation may modulate the physiological response to stress via neurohumoral activation as displayed by the fairly good indicator namely heart rate.